Diagnostic Approach to Children with Unexplained Global Developmental Delay in Pediatric Neurology Outpatient Clinic - Veronese, Airin; Osredkar, Damjan; Lovrečić, Luca; Troha Gergeli, Anja (Neuropediatrics, 2024)
Background Global developmental delay (GDD) is a common pediatric disorder that affects up to 3% of children. Due to the heterogeneous etiology of GDD, diagnostic procedures and algorithms are complex and diverse. The aim of our study was to investigate the diagnostic yield of genetic, metabolic, and imaging studies in establishing the etiology of unexplained GDD (UGDD).Methods In this retrospectively observational study, we examined the medical records of all children diagnosed with UGDD at the Department of Pediatric Neurology, University Medical Centre Ljubljana, Slovenia, between January and December 2019. We evaluated the effectiveness of various genetic, metabolic, and magnetic resonance imaging (MRI) tests in identifying the underlying cause of GDD. Additionally, we assessed subgroups of patients to determine whether any of the studied tests were particularly beneficial based on their clinical symptoms.Results A total of 123 patients met the inclusion criteria, with a median age of 4.3 years (range, 0–16 years), of which 71 (57.7%) were males. Genetic diagnosis was established in 47.1% (58/123) of patients. Metabolic laboratory testing did not identify a metabolic disease in any of the tested participants (114/123) and MRI was critical for diagnosis in only 1/81 (1.2%) patient.Conclusion Our findings strongly suggest that genetic testing surpasses MRI and metabolic testing in establishing the etiology of UGDD in a pediatric neurology outpatient setting. This information will help guide the diagnostic evaluation of these children.
Keywords: unexplained global developmental delay; diagnostic yield; genetics; MRI; metabolic screening